ANALYSIS AND IMPROVEMENT OF THE HEALTH EXAMINATION PROCESS FOR SPEEDY DIAGNOSIS IN ALAGOAS - Bezerra Lima, Alexandre; Cristina Dias de Souza, Elizabeth; Erilúcia Cruz Macêdo, Maria; Capela Fontes, Rogério (Health and Society, 2023)
The Unified Health System, as well as several public services, is currently experiencing situations related to the slowness of processes, which may be adequate, especially the advancement of technologies. In Health Units, one of the processes that need agility is related to the care of newborns, more precisely, the heel prick test. This exam is essential to monitor the possible illnesses that may appear in babies, preventing lives from being interrupted and/or limited. In this sense, the objective of the present work was to develop analysis and improve the exams performed, through the use of new technologies available, with the aim of streamlining the diagnostic process, characterizing a new flowchart for performing the exam, as well as improving service to users of the Unified Health System - SUS. To carry out the investigation, an empirical field study research was provided, with a quali-quantitative approach, in which data were collected referring to the examinations of babies in the last five years, aiming at recognizing the need to speed up the intervention and minimize and/or eliminate the delay currently presented. Thus, the results expected by the Health Units that present illnesses should be treated as soon as possible for the well-being of newborns.